2018
DOI: 10.1016/j.molcel.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

The Augmented R-Loop Is a Unifying Mechanism for Myelodysplastic Syndromes Induced by High-Risk Splicing Factor Mutations

Abstract: SUMMARY Mutations in several general pre-mRNA splicing factors have been linked to myelodysplastic syndromes (MDSs) and solid tumors. These mutations have generally been assumed to cause disease by the resultant splicing defects, but different mutations appear to induce distinct splicing defects, raising the possibility that an alternative common mechanism is involved. Here we report a chain of events triggered by multiple splicing factor mutations, especially high-risk alleles in SRSF2 and U2AF1, including el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
219
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(244 citation statements)
references
References 59 publications
12
219
5
Order By: Relevance
“…The maintenance of genomic stability is of paramount importance to living organisms including cancer cells; thus, many proteins including splicing factors and RNA surveillance factors have been known to participate in DNA damage response. 17,[30][31][32][33] Our studies have identified that CHERP/SR140 and UPF3A are novel players involved in DNA damage response, as loss of them leads to DSB and triggers spontaneous DNA damage response and cell death. It is amazing that splicing factors and RNA surveillance factors are not only connected by alternative splicing but also by functional similarity involved in genomic maintenance, although the mechanism behind them are quite different.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The maintenance of genomic stability is of paramount importance to living organisms including cancer cells; thus, many proteins including splicing factors and RNA surveillance factors have been known to participate in DNA damage response. 17,[30][31][32][33] Our studies have identified that CHERP/SR140 and UPF3A are novel players involved in DNA damage response, as loss of them leads to DSB and triggers spontaneous DNA damage response and cell death. It is amazing that splicing factors and RNA surveillance factors are not only connected by alternative splicing but also by functional similarity involved in genomic maintenance, although the mechanism behind them are quite different.…”
Section: Discussionsupporting
confidence: 89%
“…The maintenance of genomic stability is of paramount importance to living organisms including cancer cells; thus, many proteins including splicing factors and RNA surveillance factors have been known to participate in DNA damage response . Our studies have identified that CHERP/SR140 and UPF3A are novel players involved in DNA damage response, as loss of them leads to DSB and triggers spontaneous DNA damage response and cell death.…”
Section: Discussionsupporting
confidence: 84%
“…It has been well established that deregulated or impaired RNA processing results in elevated formation of R‐loops . Since hnRNP U is an important regulator of splicing, we hypothesized that the hnRNP U bound by FANCD2 at the genomic sites under replication stress has a function to suppress R‐loop levels.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that the pathological effects of spliceosome mutations are imparted through multiple mis‐spliced products simultaneously. In parallel, pathway analyses followed by functional validation revealed that splicing factor mutations distinctly converge on key cellular pathways to drive disease pathogenesis, including defects in DNA damage response and aberrant innate immune signaling . Further studies will be required to systematically address these fundamental questions, and more importantly, to identify the key players and pathways that can potentially be exploited for therapeutic purposes.…”
Section: Effects Of Somatic Mutations In Splicing Factorsmentioning
confidence: 99%